Capacity utilization in a generalized Malmquist index including environmental factors. A decomposition analysis - Torstein Bye; Annegrete Bruvoll; Jan Larsson (Statistics Norway, Research Department, 2006)
Productivity measures ignoring environmental effects may give misleading information on total productivity growth. Further, business cycles in the form of capacity utilization may also significantly influence productivity measures. In this paper, we develop an overall Malmquist productivity index and decompose changing efficiency rates into a contribution from environmental factors, capacity utilization and other traditional factors. The capacity utilization element is a contribution to the literature in that it takes into account the capacity for producing negative externalities. We decompose the frontier movements into a contribution from traditional factors and environmental factors and apply the model to a micro data set for two Norwegian industries: the pulp and paper industry and the inorganic chemistry industry. We find frontier improvements over the period included in the analysis, while the distance to the frontier has increased. Capacity utilization increased over the period and contributed to an average approach to the frontier, while environmental indicators contributed negatively. Analysis of the two industries indicates that differences between the traditional and revised efficiency measures changes are ambiguous, except from the capacity utilization element. This indicates that the environment loses when business cycles improve.
Keywords: L73; O12; O14; O33; O41; Q48; R38; 330; Emissions; Productivity change; Pulp and paper; Inorganic chemistry; Malmquist index; Frontier technology; Capacity utilization